Microplankton Community Composition Associated With Toxic Trichodesmium Aggregations in the Southwest Atlantic Ocean - Bif, Mariana Bernardi; de Souza, Márcio Silva; Costa, Luiza Dy Fonseca; Yunes, João Sarkis (Frontiers in Marine Science, 2019)
The spatial distribution and species identification of Trichodesmium was assessed during two fall cruises along the Southwest Atlantic Ocean shelf break. Organisms from the microplankton >50 μm were collected using a vertical plankton net for quantification and identification of the microplanktonic community associated with the genus. Additional sub-samples were filtered and prepared for quantification and discrimination of phycotoxins from the particulate matter using High Performance Liquid Chromatography. Physical parameters such as temperature, salinity, wind speed, and mixed layer depth were used in order to evaluate the environmental conditions at the time of sampling and correlate with Trichodesmium occurrence. Overall, Trichodesmium abundances were higher in the northernmost stations under wind speeds of <8 knots and shallow mixed layer depths <40 m. Besides frequent reports on the occurrence of T. erythraeum and T. thiebautii for this region, we identified three species as T. clevei, T. hildebrandtii, and T. radians. In the majority of stations where Trichodesmium was not the dominant organism, other microplanktonic groups were present such as centric diatoms and dinoflagellates. The toxin analysis was positive for saxitoxins predominantly when Trichodesmium was at high numbers of trichomes per liter in the stations; however, there was an inverse relationship between abundance of trichomes and toxin concentrations. Using information from the environmental variables and Trichodesmium abundance, we suggest that the toxin production might take place during the aggregation phase of trichomes at surface, and that saxitoxins could be inhibiting the growth of other microplanktonic organisms.